2018
DOI: 10.2174/1871520617666170918130126
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Properties of Sesquiterpene Lactones: A Systematic Review

Abstract: This review summarizes the reported molecular mechanisms underlying the antileukemic property of Sesquiterpene Lactones (SLs). This systematic review was registered in the PROSPERO database and conducted following the PRISMA Statements. The MeSH terms, Sesquiterpenes, Lactones and Leukemia were used in four databases (Pubmed, Web of Science, Scopus and Bireme). There were 281 studies selected, but after exclusions, due to replication (n = 172) or not following PECOS criteria (n = 24), 148 studies remained. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Regarding anticancer activity, the effect of alantolactone (1) on leukemia is well documented and was recently reviewed by Da Silva Castro et al [43]. Xu et al [44] reported a positive and significant effect (1) on B-cell acute lymphoblastic leukemia.…”
Section: Alantolactonementioning
confidence: 99%
“…Regarding anticancer activity, the effect of alantolactone (1) on leukemia is well documented and was recently reviewed by Da Silva Castro et al [43]. Xu et al [44] reported a positive and significant effect (1) on B-cell acute lymphoblastic leukemia.…”
Section: Alantolactonementioning
confidence: 99%
“…Two systematic reviews have investigated the effects of sesquiterpene lactones on cancer cells and skin cells ( da Silva Castro et al, 2018 ; da Silva et al, 2020 ); however, no systematic review has been conducted focusing on the effect of sesquiterpene lactones on cellular differentiation, to the best of our knowledge. Herein, we have conducted a systematic review on the differentiating/dedifferentiating effects of sesquiterpene lactones on various human or animal cells, evaluated in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Lactones are bioactive compounds that possess various interesting properties, e.g., antifeedant [9][10][11][12], antimicrobial [13][14][15][16][17], and cytostatic [18][19][20][21][22][23] properties. They found application in medicine, pharmacy, cosmetology, food, and agriculture.…”
Section: Introductionmentioning
confidence: 99%